Management of Information Systems in Academic Libraries in Ghana - Ocloo, P.E.D.; King, L. (Technical Services Quarterly, 2022)
Academic libraries in Ghana have adopted information systems for library functions and services. This study sought to find out how academic libraries in Ghana manage the information systems they use. Interviews and a questionnaire were used to solicit responses from nine academic libraries in Ghana. Findings revealed that majority of the libraries studied did not have an Information Systems policy, and staff were mostly not consulted before the installation of the Information Systems.
Research Article
Keywords: Information system; academic libraries; Ghana